Morphological Variation and Plant Nutrients Effects of Two Taxonomically Distant CentaureaL. Species - CELIK, SEZGIN; OZKAN, KURSAD; YUCEL, ERSIN (Asian Journal of Chemistry, 2010)
In this study, the influence of habitat on Centaurea mucronifera and C. pyrrohoplephara, whose morphological variants show obvious differences, spreading on calcareous soils of Mediterranean, Central and East Anatolia were examined. C. mucronifera and C. pyrrohoplephara are both perennials and have the height between 4 and 50 cm. The influence of nutrition elements in plant and physical and chemical properties of soils on morphological variations of C. mucronifera and C. pyrrohoplephara were determined with the models that have the highest explanation portion without multiple linkage problems on the base of model and variant and their relationships were investigated by using Stepwise Regression Analysis. It was found that there was a univariate independent model, showing the positive contribution of phosphorus content of root on plant nutrition element content and root length and for sodium content of stem on length of basal leaf and outer whorl of pappus in C. mucronifera. In C. pyrrohoplephara, between morphological characteristics and plant nutrition elements, on the base of model and variant, models having highest explanation portion without multiple relation problems were defined for variants of root length, plant length, width of basal leaf, capitula and involucrum, achene length, pappus inner whorl length. There was not any defined model determining the relationships between physical and chemical properties of soils and length and width of terminal leaf (p < 0.05). According to these results, it was found that, for C. mucronifera and C. pyrrohoplephera, physical and chemical properties of soils have an important role on the morphological structure of these species and there could be relationships between morphological structures of these taxa and the ratios of the variants of these plant nutrition element contents and also the influence of plant nutrition elements on the morphological differentiations of these species is relatively low (p < 0.05)